COVID-19 detection in CT images with deep learning: A voting-based scheme and cross-datasets analysis. (2020) - Silva, Pedro; Luz, Eduardo; Silva, Guilherme; Moreira, Gladston; Silva, Rodrigo; Lucio, Diego; Menotti, David
Abstract: Early detection and diagnosis are critical factors to control the COVID-19 spreading. A number of deep learning-based methodologies have been recently proposed for COVID-19 screening in CT scans as a tool to automate and help with the diagnosis. These approaches, however, suffer from at least one of the following problems: (i) they treat each CT scan slice independently and (ii) the methods are trained and tested with sets of images from the same dataset. Treating the slices independently means that the same patient may appear in the training and test sets at the same time which may produce misleading results. It also raises the question of whether the scans from the same patient should be evaluated as a group or not. Moreover, using a single dataset raises concerns about the generalization of the methods. Different datasets tend to present images of varying quality which may come from different types of CT machines reflecting the conditions of the countries and cities from where they come from. In order to address these two problems, in this work, we propose an Efficient Deep Learning Technique for the screening of COVID-19 with a voting-based approach. In this approach, the images from a given patient are classified as group in a voting system. The approach is tested in the two biggest datasets of COVID-19 CT analysis with a patient-based split. A cross dataset study is also presented to assess the robustness of the models in a more realistic scenario in which data comes from different distributions. The cross-dataset analysis has shown that the generalization power of deep learning models is far from acceptable for the task since accuracy drops from 87.68% to 56.16% on the best evaluation scenario. These results highlighted that the methods that aim at COVID-19 detection in CT-images have to improve significantly to be considered as a clinical option and larger and more diverse datasets are needed to evaluate the methods in a realistic scenario. Highlights: Voting-based approach extending the EfficientNet Family of deep artificial neural networks. A cross-dataset study with the two largest public datasets available. A specific data augmentation process and transfer learning for such task. A high-quality yet compact deep-learnign model for the screening of COVID-19 in CT scans. Highest accuracy (and F1-measure) to date on COVID-CT dataset and SARS-CoV-2 CT-scan dataset.